Systemic hypoxia led to little retinal neuronal loss and dramatic optic nerve glial response. (April 2020) - Mesentier-Louro, Louise Alessandra; Shariati, Mohammed Ali; Dalal, Roopa; Camargo, Alexandra; Kumar, Varun; Shamskhou, Elya Ali; de Jesus Perez, Vinicio; Liao, Yaping Joyce
Abstract: Vision loss is a devastating consequence of systemic hypoxia, but the cellular mechanisms are unclear. We investigated the impact of acute hypoxia in the retina and optic nerve. We induced systemic hypoxia (10% O2 ) in 6-8w mice for 48 h and performed in vivo imaging using optical coherence tomography (OCT) at baseline and after 48 h to analyze structural changes in the retina and optic nerve. We analyzed glial cellular and molecular changes by histology and immunofluorescence and the impact of pretreatment with 4-phenylbutyric acid (4-PBA) in oligodendroglia survival. After 48 h hypoxia, we found no change in ganglion cell complex thickness and no loss of retinal ganglion cells. Despite this, there was significantly increased expression of CCAAT-enhancer-binding protein homologous protein (CHOP), a marker of endoplasmic reticulum stress, in the retina and optic nerve. In addition, hypoxia induced obvious increase of GFAP expression in the anterior optic nerve, where it co-localized with CHOP, and significant loss of Olig2 + oligodendrocytes. Pretreatment with 4-PBA, which has been shown to reduce endoplasmic reticulum stress, rescued total Olig2 + oligodendrocytes and increased the pool of mature (CC-1 + ) but not of immature (PDGFRa+) oligodendrocytes. Consistent with a selective vulnerability of the retina and optic nerve in hypoxia, the most striking changes in the 48 h murine model of hypoxia were in glial cells in the optic nerve, including increased CHOP expression in the astrocytes and loss of oligodendrocytes. Our data support a model where glial dysfunction is among the earliest events in systemic hypoxia – suggesting that glia may be a novel target in treatment of hypoxia. Highlights: Acute systemic hypoxia led to glial response in the visual system. Hypoxia induced astrocyte stress and reactivity in the unmyelinated optic nerve. Hypoxia led to loss of oligodendrocytes in the myelinated optic nerve.